2023
DOI: 10.1007/s00586-022-07454-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a microgravity SkinSuit on lumbar geometry and kinematics

Abstract: Purpose Astronauts returning from long ISS missions have demonstrated an increased incidence of lumbar disc herniation accompanied by biomechanical and morphological changes associated with spine elongation. This research describes a ground-based study of the effects of an axial compression countermeasure Mk VI SkinSuit designed to reload the spine and reduce these changes before return to terrestrial gravity. Methods Twenty healthy male volunteers aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The sensitivity of spinal stiffness to gravitational changes and a potential link to vertebral kinematics ( Breen et al, 2023 ) suggests that its evaluation is warranted during spaceflight, but also in response to ARED use, and candidate spinal deconditioning countermeasures such as axial-loading provided by SkinSuit, as such loading has been suggested to promote spinal control on Earth ( Rathinam et al, 2013 ). Recently, the Mk VI SkinSuit ( Stabler et al, 2017 ), devised to provide ≈0.2gz axial loading ameliorated spinal elongation and back pain by ≈ 50% induced by 8-h HBF by ≈ 50% ( Green et al, 2023 ), as well as restoring lumbar mobility and lordosis following 4 h HBF ( Breen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of spinal stiffness to gravitational changes and a potential link to vertebral kinematics ( Breen et al, 2023 ) suggests that its evaluation is warranted during spaceflight, but also in response to ARED use, and candidate spinal deconditioning countermeasures such as axial-loading provided by SkinSuit, as such loading has been suggested to promote spinal control on Earth ( Rathinam et al, 2013 ). Recently, the Mk VI SkinSuit ( Stabler et al, 2017 ), devised to provide ≈0.2gz axial loading ameliorated spinal elongation and back pain by ≈ 50% induced by 8-h HBF by ≈ 50% ( Green et al, 2023 ), as well as restoring lumbar mobility and lordosis following 4 h HBF ( Breen et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional value of such changes remains to be determined ( Plehuna et al, 2022 ). Yet in another ground-based model of µg termed hyper-buoyancy flotation (HBF) developed to model stature elongation and back pain ( Green et al, 2023 ) is also associated with modulation in lumbar kinematics ( Breen et al, 2023 ). Recent parabolic flight studies have also showed a rapid increase in lumbar (L3) spine stiffness, defined as resistance to deformation of the spinal system ( Panjabi, 1992b ; Panjabi, 1992a ; Hodges et al, 2013 ; Needle et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%